Colorimetric biosensor and application thereof in colorimetric detection of campylobacter jejuni
By developing colorimetric biosensors, the capture module of magnetic nanoparticles and aptamers, as well as the binding-conducting module of iron carrier and polylysine, the specificity, sensitivity and immediacy of Campylobacter jejuni detection in the prior art were solved, and efficient and accurate detection effects were achieved.
Patent Information
- Application Number
- CN202411968721.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing Campylobacter jejuni detection methods have shortcomings in specificity, sensitivity, immediacy and simplicity, which limits its application in real-time and on-site inspections.
A colorimetric biosensor is developed, including a capture module, a binding-conduction module and a color development module. The capture module specifically captures Campylobacter jejuni through magnetic nanoparticles and modified aptamers, and the binding-conducting module stabilizes agglomerated gold nanoparticles through iron carriers and polylysine, and is detected by color and absorbance changes.
It has achieved high sensitivity, strong specificity and good stability detection for Campylobacter jejuni, and can accurately analyze the bacterial density in the sample in a short time, which is suitable for real-time detection of actual samples.
Smart Images

Figure CN119757743A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biological detection, relates to a detection method of Campylobacter jejuni, and specifically relates to a colorimetric biosensor and an application thereof in detecting Campylobacter jejuni by a colorimetric method. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Campylobacter jejuni (C.jejuni) is a zoonotic foodborne pathogen that can cause serious impacts on human life and public health. Currently, the detection methods for Campylobacter jejuni include isolation and culture, physiological and biochemical analysis, qPCR and DNA microarray, but these methods have many shortcomings in terms of specificity, sensitivity, timeliness and simplicity, which limits their application in immediate and on-site testing.
[0004] Unlabeled gold nanoparticles have unique surface plasmon resonance (SPR) properties, which can provide sensors with sensitive, naked-eye detectability through the color and absorbance changes produced by different degrees of AuNPs aggregation, and are widely used in the development of colorimetric sensors. Currently, a variety of non-crosslinked aggregation-based gold nanoparticle colorimetric biosensors have been reported, but such methods still have problems such as low sensitivity, poor specificity, poor stability, and inability to accurately quantify. Summary of the invention
[0005] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a colorimetric biosensor and its application in the colorimetric detection of Campylobacter jejuni. The colorimetric biosensor provided by the present invention can be used to detect Campylobacter jejuni, and has the advantages of high sensitivity, strong specificity, good stability, accurate quantification, etc.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] In a first aspect, a colorimetric biosensor comprises:
[0008] A capture module comprises a magnetic nanoparticle and an aptamer modified on the magnetic nanoparticle, wherein the aptamer can specifically bind to Campylobacter jejuni;
[0009] A binding-transduction module, for binding Campylobacter jejuni, comprising an iron carrier and polylysine (PL) modified on the surface of the iron carrier;
[0010] Color development module, gold nanoparticles (AuNPs) solution.
[0011] When the biosensor is working, the capture module is responsible for specifically capturing Campylobacter jejuni from the complex matrix of the actual sample, and then the binding-conducting module binds to the Campylobacter jejuni captured by the capture module. Finally, by observing the effect of different concentrations of the binding-conducting module on the aggregation degree of AuNPs, the bacterial density is indicated by the changes in the color and absorbance of the system, and their correlation is established. Among them, the siderophore is responsible for binding Campylobacter jejuni, while PL replaces the citrate anion on the surface of AuNPs through the side chain amino functional group, making the AuNPs more stably aggregated and finally converting it into a more stable colorimetric signal.
[0012] In some embodiments, the sequence of the aptamer is shown as SEQ ID NO. 1. Studies have shown that the aptamer can make the biosensor have higher specificity for Campylobacter jejuni.
[0013] In some embodiments, the capture module further comprises calcium ions, which are used to block free carboxyl groups on the surface of the capture module. Blocking free carboxyl groups by calcium ions can avoid nonspecific adsorption.
[0014] In some embodiments, the preparation method of the capture module is: prepare the magnetic nanoparticles into a dispersion, add a carboxyl activator to the dispersion, then add an aptamer, and incubate at 2 to 6°C. Studies have shown that when the concentration of the aptamer in the reaction system is 4 to 6 μg / mL, the grafting degree of the capture module is the largest, and the grafting degree is 422 to 431 ng / mg. Studies have shown that the incubation time also affects its grafting degree. When the incubation time is 15 to 16 hours, the grafting degree of the capture module is the largest.
[0015] In some embodiments, the siderophore is derived from Aureobasidium melanogenum HN6.2 strain.
[0016] In some embodiments, the molar ratio of the iron carrier to polylysine is 1: 1 to 3. Studies have shown that when the molar ratio of the iron carrier to polylysine is 1: 1.0 to 1.2, the biosensor has a higher sensitivity.
[0017] In some embodiments, the preparation method of the binding-conducting module is: after adding a carboxyl activator to a polylysine solution for activation, an iron carrier is added for amide condensation reaction, and then dialyzed to obtain the binding-conducting module.
[0018] In some embodiments, the concentration of the AuNPs solution is 1.0 to 3.0 nM. Studies have shown that under this condition, the color change is more obvious and is more conducive to the detection of the biosensor.
[0019] In another aspect, a colorimetric biosensor is used for detecting Campylobacter jejuni by colorimetry.
[0020] In some embodiments, the solution of the capture module is first incubated with the sample containing Campylobacter jejuni to be tested, then subjected to a first magnetic separation, and after removing the supernatant, the solution of the binding-conduction module is added for a second incubation, and then subjected to a second magnetic separation, and the supernatant after the second magnetic separation is added to the color development module for color development.
[0021] Specifically, the solution of the capture module has a concentration of 580-620 μg / mL. Studies have shown that the capture efficiency obtained under this condition is higher.
[0022] Specifically, the first incubation time is 11 to 13 minutes. Studies have shown that under this condition, the capture module has a better capture effect on Campylobacter jejuni.
[0023] Specifically, during the second incubation, the concentration of the binding-conducting module in the incubation system is 240-270 nM. Studies have shown that the detection under this condition has a better linear relationship and can make the detection result more accurate.
[0024] Specifically, the second incubation time is 15 to 30 minutes, preferably 15 to 16 minutes. Under this condition, it can be ensured that the binding-transduction module has a better binding effect on Campylobacter jejuni in a shorter time.
[0025] Specifically, the color development time is 4 to 5 minutes. Under this condition, the absorbance ratio is the highest and the time is shorter.
[0026] The beneficial effects of the present invention are:
[0027] In the colorimetric biosensor provided by the present invention, an aptamer is modified on the surface of magnetic nanoparticles, which can efficiently and specifically bind to Campylobacter jejuni, and can obtain Campylobacter jejuni from a sample by magnetic separation. At the same time, polylysine PL is modified on the surface of an iron carrier to form a bifunctional binding-conduction module that recognizes and binds to Campylobacter jejuni and stabilizes the agglomerated AuNPs. Based on the colorimetric biosensor, Campylobacter jejuni in a sample can be specifically detected; and its detection method enhances the color response of AuNPs, thereby improving the specificity and sensitivity of the sensor.
[0028] Experimental studies have shown that the colorimetric biosensor provided by the present invention can be used to detect Campylobacter jejuni in samples. The total detection time is 31 minutes, and the naked eye observable detection limit is 10 2 CFU / mL, and the theoretical detection limit is 1 CFU / mL. In the actual sample detection of simulated chicken and milk, the actual detection limit is 7 CFU / mL, and the results prove that the sensor can be used for real-time detection of actual samples. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0030] Figure 1 Transmission electron micrograph (A) and particle size distribution (B) of MNPs in Example 1 of the present invention;
[0031] Figure 2 is the UV-visible absorption spectra of MNPs and Apt-MNPs in Example 1 of the present invention;
[0032] Figure 3 The agarose gel electrophoresis diagram of Apt-MNPs in Example 1 of the present invention, lane M is 50 bp DNA ladder, lane 1 is Apt, lane 2 is Apt-MNPs, and from top to bottom are 500 bp, 400 bp, 350 bp, 300 bp, 250 bp, 200 bp, 150 bp, 100 bp, 50 bp;
[0033] Figure 4 is the infrared spectrum of Apt-MNPs in Example 1 of the present invention;
[0034] Figure 5 This is a graph showing the 16S rDNA tag analysis of bacteria captured by Ca / Apt-MNPs in Example 1 of the present invention. Columns marked with different letters have significant differences, abc, n=3, P<0.05;
[0035] Figure 6 This is an optimization diagram of the grafting degree of Ca / Apt-MNPs in Example 1 of the present invention;
[0036] Figure 7 This is an optimization diagram of the Ca / Apt-MNPs binding time in Example 1 of the present invention;
[0037] Figure 8 This is the optimization diagram of the amount of Ca / Apt-MNPs used in Example 1 of the present invention. Columns marked with different letters have significant differences, abcd, n=3, P<0.05;
[0038] Fig. 9 is FsC[Fe 3+ ]-PL characterization diagram, A is FsC[Fe 3+ ]-PL FTIR, B is FsC[Fe 3+ ]-PL XPS spectrum, C is FsC[Fe 3+ ]-PL C1s spectrum, D is FsC[Fe3+ ]-N1s spectrum of PL;
[0039] Fig.10 is FsC[Fe 3+ ]-PL Zeta potential result diagram, columns marked with different letters have significant differences, abcde, n=3, P<0.05;
[0040] Fig.11 is FsC[Fe 3+ ]-PL in FsC[Fe 3+ ] and PL molar ratio, columns marked with different letters have significant differences, abc, n = 3, P < 0.05;
[0041] Fig.12 is FsC[Fe 3+ ]-PL and FsC[Fe 3+ ]-PL-FAM fluorescence intensity graph, columns marked with different letters have significant differences, ab, n=3, P<0.05;
[0042] Fig.13 is FsC[Fe 3+ ]-Laser scanning confocal microscopy images after incubation of PL-FAM with bacteria;
[0043] Fig.14 is a transmission electron microscopy image of AuNPs in Example 2 of the present invention;
[0044] Fig.15 The particle size distribution diagram of AuNPs dispersion (A) and aggregation (B) in Example 2 of the present invention;
[0045] Fig.16 Zeta potential of AuNPs dispersion (A) and aggregation (B) in Example 2 of the present invention, columns marked with different letters have significant differences, ab, n=3, P<0.05;
[0046] Fig.17 This is the UV-visible absorption spectrum of AuNPs in Example 2 of the present invention;
[0047] Fig.18 Graph showing the optimization results of the working concentration of gold nanoparticles in Example 2 of the present invention, A is the absorption spectrum of AuNPs at different concentrations, and B is the absorbance ratio ΔA625 / A520 of AuNPs;
[0048] Fig.19 This is a schematic diagram of the working principle of the sensor in Example 2 of the present invention;
[0049] Fig. 20This is a diagram showing the verification result of the working principle of the sensor in Example 2 of the present invention;
[0050] Fig.21 is FsC[Fe 3+ ]-PL-1 working concentration optimization results, A is different FsC[Fe 3 + ]-The effect of PL-1 concentration on AuNPs, B is the absorbance ratio of AuNPs ΔA625 / A520;
[0051] Fig. 22 is FsC[Fe 3+ ]-PL-1 detection sensitivity result diagram, A is the absorption spectrum of the biosensor detecting Campylobacter jejuni; B is the absorbance ratio ΔA625 / A520 of AuNPs;
[0052] Fig.23 is FsC[Fe 3+ ]-PL-2 working concentration optimization results, A is different FsC[Fe 3 + ]-The effect of PL-1 concentration on AuNPs, B is the absorbance ratio of AuNPs ΔA625 / A520;
[0053] Fig.24 is FsC[Fe 3+ ]-PL-2 detection sensitivity result diagram, A is the absorption spectrum of the biosensor detecting Campylobacter jejuni; B is the absorbance ratio ΔA625 / A520 of AuNPs;
[0054] Fig.25 is FsC[Fe 3+ ]-PL-3 working concentration optimization results, A is different FsC[Fe 3 + ]-The effect of PL-1 concentration on AuNPs, B is the absorbance ratio of AuNPs ΔA625 / A520;
[0055] Fig.26 is FsC[Fe 3+ ]-PL-3 detection sensitivity result diagram, A is the absorption spectrum of the biosensor detecting Campylobacter jejuni; B is the absorbance ratio ΔA625 / A520 of AuNPs;
[0056] Fig. 27 The Campylobacter jejuni in Example 2 of the present invention binds to FsC [Fe 3+ ]-PL efficiency, columns marked with different letters have significant differences, abc, n=3, P<0.05;
[0057] Fig.28 This is a graph showing the optimization results of the incubation time of Ca / Apt-MNPs and C.jejuni in Example 3 of the present invention;
[0058] Fig.29 is FsC[Fe 3+ ]-PL-1 and C.jejuni incubation time optimization results;
[0059] Fig.30 This is a diagram showing the optimization results of the AuNPs color development time in Example 3 of the present invention;
[0060] Fig.31 Result diagrams of the detection limit of the sensor in Example 3 of the present invention, A is an absorption spectrum diagram of the biosensor detecting Campylobacter jejuni, and B is a linear standard curve of C. jejuni;
[0061] Fig.32 The specific result diagram of the biosensor detecting Campylobacter jejuni in Example 3 of the present invention, A is the absorption spectrum, B is the absorbance ratio ΔA625 / A520, and the columns marked with different letters have significant differences, ab, n=3, P<0.05. DETAILED DESCRIPTION
[0062] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0063] Example 1 Preparation and working conditions of capture module
[0064] Preparation and characterization of MNPs
[0065] Add 0.527g of ferric chloride hexahydrate powder and 0.35g of sodium citrate dihydrate to a 50ml beaker, then measure 35mL of ethylene glycol and stir magnetically under water bath heating conditions to obtain an orange-yellow solution. Weigh 2.1g of sodium acetate trihydrate and continue to add it to the beaker, and stir magnetically until it is completely dissolved. Then put the mixed solution into a polytetrafluoroethylene-lined high-pressure reactor and hydrothermally react in an oven at 200°C for 12h. After the reaction is completed, cool naturally to room temperature, take out the reactor, and obtain a brown or black reactant. Then transfer the reactant to a centrifuge tube, use a magnetic stand to remove the supernatant, and obtain magnetic particles. Wash with deionized water and ethanol alternately several times until the supernatant is colorless. Finally, the treated Fe 3 O 4 Freeze drying of magnetic nanoparticles (MNPs).
[0066] Transmission electron microscopy was used to analyze the morphology and particle size. Figure 1 As shown in A, from Figure 1 As can be seen in A, the MNPs prepared by this method are spherical and uniformly distributed. Figure 1 B shows the particle size and distribution of MNPs, which are between 8-15 nm, with an average particle size of 11.61±2.17 nm, and a relatively uniform distribution.
[0067] Synthesis and Characterization of Aptamer-MNPs (Aptamer-modified Magnetic Nanoparticles, Apt-MNPs)
[0068] Weigh 10 mg of MNPs into a glass vial, wash with deionized water three times, and resuspend in 10 mL of 15 mM MES buffer (pH 6.0) after magnetic separation, and perform low-temperature ultrasonic dispersion until the MNPs are fully dispersed. Then add 10 mg of EDC·HCl and 12 mg of NHS to the solution, and perform rotation activation at 25°C for 30 min. After activation, perform magnetic separation, wash with deionized water three times, and quickly transfer to 10 ml of PBS buffer (pH 7.4), add 800 nmol / mg of aptamer with amino group modified at 5' end, and then move to 4°C chromatography cabinet for rotation incubation for 16 h. After the reaction, place the product on a magnetic stand for magnetic separation, remove the supernatant, wash with deionized water three times, and store in a 4°C refrigerator.
[0069] The sequence of the aptamer with amino group modified at the 5' end is as follows:
[0070] NH 2 -CGCGTGTCTGCTGTCAATCGCAAGGTCCATGTCCCGCG, as shown in SEQ ID NO.1.
[0071] The product characterization experiment includes: first, the synthesis of Apt-MNPs is preliminarily characterized by ultraviolet visible absorption spectroscopy (UV-Vis); then, it is further characterized by electrophoretic mobility assay (EMSA). Finally, the product is freeze-dried, and then Fourier transform infrared spectroscopy (FT-IR) is used for the final characterization of Apt-MNPs. In order to avoid the nonspecific adsorption phenomenon caused by the presence of carboxyl groups on the surface of Apt-MNPs, the free carboxyl groups remaining on its surface are blocked. The operation method is as follows: First, the prepared 10mg Apt-MNPs are magnetically separated, washed 3 times with PBS buffer, and then placed in a 4°C environment and incubated with 5% CaCl 2 Incubate in 10 mL PBS buffer for 60 min. After incubation, wash with deionized water for 3 times to obtain Ca / Apt-MNPs. After treatment, store them in a refrigerator at 4 °C.
[0072] The synthesized product Apt-MNPs was preliminarily analyzed by ultraviolet-visible absorption spectroscopy (UV-Vis). Figure 2 As shown. Figure 2 It can be seen that the single MNPs have no characteristic absorption peak in the wavelength range of 200-800nm, while the synthesized Apt-MNPs have a new characteristic absorption peak at 260nm, which can confirm that Aptamer has been successfully grafted on the surface of MNPs, that is, the capture module Apt-MNPs has been successfully synthesized. This is because the conjugated double bonds contained in the purine ring and pyrimidine ring of Aptamer have strong ultraviolet absorption at 260nm.
[0073] Apt-MNPs were further validated by electrophoretic mobility shift assay (EMSA). Figure 3 As shown, Apt-MNPs showed a retardation phenomenon in agarose gel electrophoresis, indicating that the aptamer of Campylobacter jejuni has been successfully modified on the surface of the magnetic particles.
[0074] The Apt-MNPs product was analyzed by FT-IR spectroscopy. Figure 4 As shown, Apt-MNPs have a peak at 2970 cm -1 The new characteristic peaks appearing near 1395.6cm are attributed to the CH stretching vibration peak, indicating that there are a large number of CH bonds in the product. -1 The sharp characteristic peaks near 1052-1087cm are attributed to NH vibration, which confirms the existence of a large number of NH bonds in the product. -1 The new characteristic peaks in the range come from PO 2- The asymmetric stretching vibration of the product further proves that the product contains the phosphate group unique to the aptamer. These newly emerged characteristic peaks indicate that the synthesized Apt-MNPs introduce a large number of amino groups and phosphate groups from the aptamer, thus confirming the successful synthesis of the sensor capture module Apt-MNPs.
[0075] Specificity of Ca / Apt-MNPs
[0076] 1 mg of Ca / Apt-MNPs was first dispersed by low-temperature ultrasonication, washed twice with PBS buffer, and then placed in a bacterial culture medium with a bacterial density of 1.0×10 7CFU / mL of bacterial communities (Campylobacter jejuni, Bifidobacterium, Escherichia coli, Salmonella enteritidis, Streptococcus gordonii, Listeria monocytogenes, Lactobacillus casei, Lactobacillus johnsonii, Enterococcus faecalis, Ralstonia pekinensis, and Shigella dysenteriae). Incubate at 37°C for 30 minutes. After the incubation, place it on a magnetic stand for magnetic separation and wash it twice with deionized water to remove the supernatant. Then the obtained product was used as a PCR template for 16SrDNA PCR amplification. The amplified fragment was recombined into the pMDTM19-T simple vector, which was then transformed into Escherichia coli DH5α. Finally, 200 clones were selected and sent to Shanghai Shenggong Biological Company for Sanger sequencing. Finally, the BLAST (Basic Local Alignment Search Tool) in the website NCBI was used to compare the sequence with the obtained sequencing results to further determine the species of the 200 clones and record the determined species.
[0077] The results are as follows Figure 5 As shown, Campylobacter jejuni accounts for 94.5%, while other bacteria account for less than 6%. It can be seen that the binding ability of Ca / Apt-MNPs to Campylobacter jejuni is significantly better than that to other bacteria, and the difference is significant. Therefore, it can be proved that the synthesized Ca / Apt-MNPs have significant specificity and can be used as a recognition and capture module for Campylobacter jejuni.
[0078] Optimization of Grafting Degree of Ca / Apt-MNPs
[0079] The magnetic nanoparticles (MNPs) were activated with EDC·HCl / NHS, and then different concentrations (0.5, 1, 3, 4, 5, 6 μg / mL) of 5'-end modified amino aptamers were added to bind to them. The aptamers were rotated and incubated in 1 ml PBS buffer (pH 7.4) at 4°C for 16 h. After the incubation, magnetic separation was performed to remove the unreacted aptamers, and then SYBR Green II dye was used for quantitative analysis.
[0080] like Figure 6 As shown in the figure, the changes in the surface grafting degree of MNPs when synthesizing Ca / Apt-MNPs when different amounts of Aptamer are added. Figure 6 It can be seen that when the Aptamer concentration is 4 μg / mL, the Aptamer grafting degree on the MNPs surface reaches a maximum of 422 ng / mg. Even if more aptamers are added, the grafting amount on the magnetic particle surface no longer increases significantly. Therefore, it is determined that the maximum grafting degree of Ca / Apt-MNPs is 422 ng / mg.
[0081] The magnetic nanoparticles (MNPs) were activated, and then the optimal concentration of aptamers was added and bound for 4, 8, 12, 16, 20, 24, and 28 hours at 4°C. After the incubation, magnetic separation was performed to remove the unbound aptamers, and SYBR Green II dye was used for quantitative analysis to study the effect of binding time on the grafting degree of the aptamer.
[0082] Depend on Figure 7 It can be seen that when the aptamer input amount is 4 μg / mL, the grafting degree of the aptamer on the surface of the magnetic particles increases with the increase of binding time, and reaches the maximum at 15h, which is 431ng / mg. Even if the binding time is increased, the grafting degree does not increase. Therefore, the optimal synthesis reaction time of Ca / Apt-MNPs is 15h.
[0083] Optimization of working concentration of Ca / Apt-MNPs
[0084] Ca / Apt-MNPs with concentrations of 100, 200, 400, 600, 800 and 1000 μg / mL were mixed with 1 mL of bacterial culture medium with a density of 1.0×10 7 CFU / mL of Campylobacter jejuni was vortexed and incubated in a constant temperature oscillator at 37°C for 30 minutes. After the incubation, magnetic separation was performed to separate the supernatant. Subsequently, the number of Campylobacter jejuni remaining in the supernatant was determined using the qPCR absolute quantitative method, and finally the capture efficiency of Ca / Apt-MNPs for Campylobacter jejuni was calculated.
[0085] The results are as follows Figure 8 As shown in the figure, when the concentration of Ca / Apt-MNPs in the system reached 600 μg / mL, the capture efficiency reached 99%, and there was no significant difference in capture efficiency with the increase of concentration. Therefore, the optimal concentration of Ca / Apt-MNPs for capturing Campylobacter jejuni is 600 μg / mL.
[0086] Example 2 Preparation and working conditions of the binding-conduction and color development module
[0087] Siderophore (FsC[Fe 3+ Preparation of
[0088] Aureobasidium melanogenum HN6.2 strain was cultured in 50 mL of iron-deficient medium to produce a large amount of iron carriers. After the culture was completed, the cells and the supernatant were separated by centrifugation, and the supernatant was the extracellular iron carrier solution. The extracellular iron carriers were separated using Amberlite XAD-16 resin, and the steps were as follows:
[0089] (1) Add excess ferrous sulfate to the extracellular iron carrier solution and place at 4°C overnight. Centrifuge at 12,000 × g for 10 min and retain the supernatant.
[0090] (2) The extracellular iron carrier solution was added to the Amberlite XAD-16 resin column for adsorption.
[0091] (3) After adsorption, remove excess iron ions by eluting with ultrapure water 3 times the volume of the resin bed.
[0092] (4) The iron carrier was eluted with 1 resin bed volume of methanol.
[0093] (5) The obtained iron carrier methanol eluate was concentrated, freeze-dried and stored at 4°C.
[0094] FsC[Fe 3+ Preparation and characterization of ]-PL
[0095] First, 1 mg of ε-PL was weighed and dissolved in 10 ml of 15 mM MES buffer (pH 6.0), and then 1 mg of EDC·HCl and 1.5 mg of NHS were added. The mixture was activated in a rotary mixer at room temperature for 20 min. After activation, 0.5 mg of FsC[Fe 3+ ] and continued to be placed in a rotating mixer for 24 hours. After the reaction was completed, the mixed solution was dialyzed for 24 hours using a dialysis bag with Mw = 3.5-5KD to remove unreacted FsC [Fe 3+ ] and ε-PL. The remaining solution was then transferred to an 8KD dialysis tape and dialyzed for 6 hours to separate the product FsC[Fe 3+ ]-PL-1. The remaining solution in the dialysis bag was transferred to a 10KD ultrafiltration centrifuge tube and centrifuged at 4000 rpm for 15 min to separate the product FsC[Fe 3+ ]-PL-2, and the supernatant was finally recovered as FsC[Fe 3+ ]-PL-3, successfully isolated and purified three different PL modified FsC[Fe 3+ ]-PL.
[0096] First, the products were freeze-dried and the three FsC[Fe 3+ ]-PL products were preliminarily characterized; subsequently, they were further analyzed and characterized using a Malvern nanoparticle size potentiometer. Finally, the three FsC[Fe 3+ ]-PL products FsC[Fe 3+ ] and ε-PL, and further characterize and analyze the structure of the product.
[0097] The results of Fourier transform infrared spectroscopy are as follows Fig. 9 As shown in A, 3600-3100cm -1 The broad peak in the range is the amino group (-NH 2 , -NH) stretching vibration peaks, and are enhanced with further modification of PL. -1 and 1562cm -1 There are also two characteristic peaks at the junction, which are attributed to the stretching vibration of the carbonyl group (C=O) and the bending vibration of the nitrogen-hydrogen bond (NH). 3+ ]-PL, which can preliminarily prove that PL is successfully modified in FsC[Fe 3+ ]surface.
[0098] XPS characterization Fig. 9 As described in B, with further modification of PL, FsC[Fe 3+ ]-PL surface nitrogen content also increases. 3+ ]-PL C1s spectrum shows three different types of carbon elements, namely CC at 285.0 eV, CN at 286.0 eV, and COO at 287.8 eV ( Fig. 9 C). Spectrum of N1s ( Fig. 9 D) shows two peaks centered at 399.5 eV and 401.1 eV, respectively (attributed to C-NH 2 and NC=O)). FsC[Fe 3+ ]-PL XPS high-resolution C1s and N1s spectra show that in FsC[Fe 3+ ]-PL surface has a large number of nitrogen-containing groups, which can further prove that PL has been successfully modified on FsC[Fe 3+ ]surface.
[0099] FsC[Fe 3+ ]-PL surface charge results are as follows Fig.10 As shown, FsC[Fe 3+ ], PL, FsC[Fe 3+ ]-PL-1, FsC[Fe 3+ ]-PL-2, FsC[Fe 3+ ]-PL-3 had a Zeta potential of +2.41, +8.5, +11.5, +21.4, and +31.6 mV, respectively. 3+ ] and PL, FsC[Fe 3+ The positive charge on the surface of PL increased with the increase of PL modification amount, which can preliminarily prove that this experiment has successfully separated and purified FsC[Fe3+ ]-PL.
[0100] The iodine oxidation method and methyl orange colorimetry were used to detect FsC[Fe 3+ ]-PL-1, FsC[Fe 3+ ]-PL-2, FsC[Fe 3 + ]-PL-3 FsC[Fe 3+ ] and PL molar ratio, the results are as follows Fig.11 As shown, FsC[Fe 3+ ]-PL-1, FsC[Fe 3+ ]-PL-2, FsC[Fe 3+ ]-PL-3 FsC[Fe 3+ ] and PL are approximately 1:1, 1:2, and 1:3, respectively.
[0101] FsC[Fe 3+ ]-PL targeting Campylobacter jejuni
[0102] Weigh 1.0 mg FsC[Fe 3+ ]-PL and 2 mg 6-carboxyfluorescein (6-FAM) were dissolved in 1 ml 15 mM MES buffer (pH 6.0), followed by the addition of 3 mg EDC·HCl and 3.5 mg NHS, which were placed in a 25°C constant temperature oscillator under light-proof conditions and incubated at 950 rpm for 2 h. After the incubation, the sample was placed in a 4°C chromatography cabinet and dialyzed for 24 h with a Mw=3500 dialysis bag to remove unreacted dye. The sample was freeze-dried to obtain 6-FAM dye-labeled FsC[Fe 3+ ]-PL-FAM conjugate.
[0103] Verification of FsC[Fe 3+ ]-PL-FAM targeting Campylobacter jejuni
[0104] Campylobacter jejuni was picked from the BHI blood plate, resuspended in 1 mL PBS buffer (pH 7.4), centrifuged at 12000 rpm for 1 min, washed 2-3 times with PBS buffer to remove the culture medium and impurities, then resuspended in PBS buffer and adjusted the OD 600 =1.0, the bacterial density is 1.0×10 8 CFU / mL, diluted to 1.0×10 7 CFU / mL. Then, 0.5 mg FsC[Fe 3+ ]-PL-FAM and 1mL bacterial density is 1.0×10 7jejuni with CFU / mL, and the control group added an equal amount of 6-FAM, and the mixture was incubated at 37°C constant temperature oscillator at 950rpm for 30min. After the incubation, centrifugation and washing were repeated 2-3 times to remove the unbound fluorescent probe, and then the bacteria were suspended in PBS buffer. Finally, the bacterial suspension was dropped on a glass slide, sealed with a cover glass, and the sample was immediately placed under a confocal microscope with an excitation wavelength of 492nm and an emission wavelength of 514nm for observation to obtain an image of bacterial cells being fluorescently labeled.
[0105] Fig.12 Fluorescently labeled and unlabeled FsC[Fe 3+ ]-PL fluorescence intensity comparison, FsC[Fe 3+ ]-PL, the fluorescence intensity was significantly enhanced, and there was a significant difference between the two fluorescence intensities, indicating that 6-FAM has been combined with FsC[Fe 3+ ]-PL has been successfully coupled.
[0106] Fig.13 The results show that 6-FAM, FsC[Fe 3+ ]-FAM, PL-FAM, FsC[Fe 3+ ]-PL-FAM binding to Campylobacter jejuni, among which 6-FAM, FsC[Fe 3+ ]-FAM and PL-FAM were used as the control group. By observing the binding of the experimental group and the control group to Campylobacter jejuni in the bright field (BF), fluorescence field (FF) and merged images (Merge), this study drew the following conclusions: From the ac and de images, it can be seen that after incubation of PL-FAM and 6-FAM with Campylobacter jejuni, there was no fluorescence on the surface of Campylobacter jejuni, indicating that PL-FAM and 6-FAM have no affinity for Campylobacter jejuni. From the gi and jl images, it can be seen that FsC[Fe 3+ ]-FAM, FsC[Fe 3+ After incubation of Campylobacter jejuni with FsC-PL-FAM, strong green fluorescence was observed on the surface of Campylobacter jejuni, indicating that FsC[Fe 3+ ]-FAM, FsC[Fe 3+ ]-PL-FAM can bind to Campylobacter jejuni, thus proving that FsC[Fe 3+ ] and prepared FsC[Fe 3+ ]-PL is targeted to Campylobacter jejuni.
[0107] Preparation and characterization of gold nanoparticles
[0108] First, prepare 50 mL of HAuCl with a concentration of (0.01%, w / v)4 , add to a 100mL round-bottom flask, stir magnetically in an oil bath and heat to boiling, then quickly add 2mL of sodium citrate aqueous solution with a concentration of (1%, w / v). Keep boiling and stirring for 30 minutes until the color of the solution changes from light yellow to wine red. After the reaction is completed, cool naturally to room temperature, filter the above solution with a 0.22μm filter membrane to remove the unreacted reducing agent. Finally, store the solution in a brown reagent bottle and place it at 4℃ for use. The morphology and particle size distribution of the synthesized AuNPs were analyzed and characterized by transmission electron microscopy, UV-visible absorption spectrophotometer, and Malvern nanoparticle size potentiometer. The molar concentration of the prepared AuNPs is 1.87nM, calculated by Beer's law (the molar extinction coefficient at 520nm is 2.78×10 8 (M -1 cm -1 )).
[0109] Transmission electron microscopy results Fig.14 As shown, the prepared AuNPs have good dispersion, an average particle size of about 35 nm, and are all spherical nanoparticles.
[0110] The prepared AuNPs solution was diluted to an appropriate concentration and the concentrations of AuNPs without and without FsC[Fe 3+ ]-PL AuNPs and the addition of FsC[Fe 3+ ]-PL particle size. Fig.15 As shown in A, no FsC[Fe 3+ ]-PL AuNPs were dispersed with an average particle size of 34.78 ± 2.31 nm; Fig.15 B, while adding FsC[Fe 3+ ]-PL, the average particle size of AuNPs increased to 447.4±4.54nm. This phenomenon indicates that FsC[Fe 3+ The addition of ]-PL caused the AuNPs to agglomerate.
[0111] The Zeta potential characterization results of the prepared AuNPs are shown in Fig.16 As shown in Figure 2, the Zeta potential of AuNPs when dispersed is -30.5±0.28 mV, while that of FsC[Fe 3+ ]-PL induced aggregation of AuNPs increased to -5.61±0.74 mV. The reason for the change in Zeta potential is that FsC[Fe 3+ The positive charge on the ]-PL surface neutralizes the negative charge on the AuNPs surface.
[0112] The UV-visible absorption spectra of AuNPs solution are shown in Fig.17As shown, at a wavelength of 400-750 nm, AuNPs have a single characteristic absorption peak at 520 nm, which further proves the uniformity of the particle size of the prepared AuNPs.
[0113] Optimization of gold nanoparticle working concentration
[0114] The AuNPs stock solution was placed in a centrifuge and centrifuged at 12000 rpm for 15 min. The concentrations were then concentrated to 0.93, 1.87, 2.80, 3.74, 4.68, 5.61, 6.55, and 7.48 nM, 100 μL of each was taken, and then 100 μL of a certain concentration of FsC[Fe 3+ ]-PL, vortexed and allowed to develop color for 5 min, and finally placed in a 96-well plate and measured using an ELISA reader for UV-visible absorption spectra at 400-750 nm.
[0115] The results are as follows Fig.18 As shown in Figure A, in a solution with a higher concentration of AuNPs, the absorbance at 625 nm is much lower than that at 520 nM, and the absorbance ratio (ΔA625 / A520) is less than 1 ( Fig.18 B), which indicates that FsC[Fe 3+ ]-PL does not cause AuNPs to aggregate in high-concentration AuNPs solutions. However, as the concentration of the AuNPs solution decreases, the change in the absorbance ratio becomes more and more obvious. When the concentration of the AuNPs solution decreases to 2.8nM, the ratio reaches the maximum and the color change is most obvious. Therefore, the optimal working concentration of the AuNPs solution was finally determined to be 2.80nM.
[0116] Verification of sensor detection principle
[0117] First, Ca / Apt-MNPs with an optimal working concentration of 600 μg / mL were mixed with 1.0 mL of 1.0×10 7 CFU / mL of Campylobacter jejuni were added to a 2 mL eppendorf tube and incubated in a 37°C constant temperature oscillator for 30 min. After incubation, magnetic separation was performed, the supernatant was removed, and the cells were washed 2-3 times with PBS buffer and ddH 2 O and washed twice. Then, 200 μL of 280 mM FsC[Fe 3+ ]-PL, and incubate again with shaking for 30 min. After the incubation, magnetic separation was performed, 100 μL of the supernatant was taken and added to 100 μL of AuNPs solution for color development for 5 min, and finally placed in a 96-well plate to measure the UV-visible absorption spectrum at 400-750 nm.
[0118] Working principle of the sensor: Fig.19As shown in the figure, the capture module Ca / Apt-MNPs is first used to specifically capture Campylobacter jejuni. Then a certain concentration (higher than the critical concentration of AuNPs) of the binding-transduction module FsC[Fe 3 + ]-PL, due to FsC[Fe 3+ ]-PL iron carrier FsC[Fe 3+ ] can specifically bind to Campylobacter jejuni, resulting in FsC[Fe 3+ Finally, by observing the different concentrations of FsC[Fe 3+ ]-PL-1 affects the aggregation degree of AuNPs, and the bacterial density is indicated by the changes in system color and absorbance, and their correlation is established.
[0119] Test results such as Fig. 20 As shown, when Campylobacter jejuni is present, due to the FsC[Fe 3+ ]-PL iron carrier FsC[Fe 3+ ] can specifically bind to Campylobacter jejuni, resulting in the FsC[Fe 3+ ]-PL concentration decreases. At this time, the FsC[Fe 3+ ]-NH on the PL surface 2 It is not enough to completely replace the citrate on the surface of AuNPs, and the electrostatic repulsion between AuNPs particles is not reduced. The electrostatic repulsion is greater than the van der Waals force. AuNPs are still in a dispersed state without agglomeration. The color is wine red, and the absorption peak at 520nm does not show a red shift ( Fig. 20 red curve). However, when Campylobacter jejuni was absent, the FsC[Fe 3+ ]-PL concentration remains unchanged, the FsC[Fe 3+ ]-NH on the PL surface 2 It is enough to completely replace the citrate on the surface of AuNPs, reduce the electrostatic repulsion between AuNPs particles, cause AuNPs to agglomerate, the solution color changes from wine red to blue purple, the absorption peak of AuNPs at 520nm is red-shifted, and a new absorption peak is generated at 625nm ( Fig. 20 Blue curve). Therefore, the qualitative and quantitative detection of Campylobacter jejuni can be achieved by means of the changes in the color and absorption spectrum of AuNPs.
[0120] FsC[Fe 3+ ]-Optimization of PL grafting degree
[0121] First, Ca / Apt-MNPs with an optimal working concentration of 600 μg / mL were magnetically separated and then precipitated with ddH 2O for 3 times, and then 500 mM FsC[Fe 3+ ]-PL-1, 250 mM FsC[Fe 3+ ]-PL-2, 150 mM FsC[Fe 3+ ]-PL-3, incubated in a constant temperature oscillator at 37°C for 30 min, and after incubation, magnetic separation was performed, and the remaining FsC[Fe 3+ ]-PL concentration, and the blank substrate concentrations of the three binding-transduction modules were calculated based on this.
[0122] FsC[Fe 3+ The blank substrate concentration of ]-PL-1 was 24 mM, and the FsC[Fe 3+ ]-PL-2 blank substrate concentration was 16 mM, FsC[Fe 3+ The blank substrate concentration of ]-PL-3 was 7 mM.
[0123] FsC[Fe 3+ ]-PL-1 working concentration optimization
[0124] First, 100 μL of AuNPs with the best working concentration was mixed with 100 μL of FsC[Fe 3+ ]-PL-1 solution was vortexed to make the final concentration (0, 20, 40, 60, 80, 100, 120, 140, 160, 180, 200, 220, 240, 260 mM). Then vortexed, color developed for 5 min at room temperature, and finally placed in a 96-well plate and measured using an ELISA reader at 400-750 nm. When the ratio of AuNPs to A625 / A520 reached the maximum, FsC[Fe 3+ ]-PL-1 concentration is the optimal concentration for aggregation of AuNPs.
[0125] like Fig.21 As shown in A, with the FsC[Fe 3+ ]-PL-1 concentration increases, the absorption peak at 520nm in the UV-visible absorption spectrum of AuNPs gradually red-shifts to 625nm, the absorbance ratio (ΔA625 / A520) gradually increases, and the color gradually changes from wine red to blue purple. 3+ When the concentration of ]-PL-1 reached 240 nM, AuNPs were completely aggregated, the system became stable, and the absorbance ratio (ΔA625 / A520) no longer increased (e.g. Fig.21 B) In the concentration range of 60-240 nM, FsC[Fe 3+]-PL-1 has a good linear relationship with the aggregation degree of AuNPs, the linear equation is y=0.069x+0.0398, and the correlation coefficient is 0.9906. 3+ ]-PL-1 concentration was considered to be the optimal concentration for inducing AuNPs aggregation.
[0126] In the actual detection of Campylobacter jejuni, in order to eliminate the negative charge of the Ca / Apt-MNPs surface aptamer on FsC[Fe 3+ ]-PL-1, ultimately determining the FsC[Fe 3+ The optimal working concentration of ]-PL-1 was 264 nM.
[0127] FsC[Fe 3+ ]-PL-1 Detection Sensitivity
[0128] First, 600 μg / mL Ca / Apt-MNPs and 1.0 mL of bacteria with a density of 1.0×10 7 , 1.0×10 6 , 1.0×10 5 , 1.0×10 4 , 1.0×10 3 , 1.0×10 2 jejuni with 1.0×10,0 CFU / mL were vortexed and incubated in a constant temperature oscillator at 37°C for 30 min. After the incubation, magnetic separation was performed, the supernatant was removed, and the cells were washed 2-3 times with PBS buffer and ddH 2 O and washed twice. Add 200 μL of the optimal working concentration of FsC[Fe 3+ ]-PL-1, incubated in a constant temperature oscillator at 37°C for 30 minutes. After the incubation, magnetic separation was performed, and 100 μL of the supernatant and 100 μL of the AuNPs solution were vortexed and mixed respectively. The color was developed for 5 minutes, and finally the plates were placed in a 96-well plate to measure the UV-visible absorption spectrum at 400-750 nm.
[0129] like Fig. 22 As shown in the figure, with the increase of bacterial density, the absorption peak at 520nm in the UV-visible absorption spectrum of AuNPs gradually increased, the absorbance ratio (ΔA625 / A520) gradually decreased, the aggregation degree of AuNPs gradually weakened, tended to be more dispersed, and the color gradually changed from blue-purple to wine red. 7 In the CFU / mL range, there is a good linear relationship between the logarithm of bacterial density and the absorbance ratio of AuNPs (ΔA625 / A520), and a linear regression curve ( Fig. 22B), which conforms to the linear regression equation y = -0.1245x + 1.3239, R 2 =0.9819. This proves that FsC[Fe 3+ ]-PL-1 assembled sensors showed better working performance and higher sensitivity in actual detection.
[0130] FsC[Fe 3+ ]-PL-2 working concentration optimization
[0131] First, 100 μL of AuNPs with the best working concentration was mixed with 100 μL of FsC[Fe 3+ ]-PL-2 solution was vortexed to make the final concentration (0, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110 mM). Then vortexed, color developed for 5 min at room temperature, and finally placed in a 96-well plate and measured using an ELISA reader at 400-750 nm. When the ratio of AuNPs to A625 / A520 reached the maximum, FsC[Fe 3+ ]-PL-2 concentration is the optimal concentration for aggregating AuNPs.
[0132] like Fig.23 As shown in A, with the FsC[Fe 3+ ]-PL-2 concentration increases, the absorption peak at 520nm in the UV-visible absorption spectrum of AuNPs gradually red-shifts to 625nm, the absorbance ratio (ΔA625 / A520) gradually increases, and the color gradually changes from wine red to blue purple. 3+ When the concentration of ]-PL-2 reached 90 nM, AuNPs were completely aggregated, the system became stable, and the absorbance ratio (ΔA625 / A520) no longer increased (e.g. Fig.23 B) In the concentration range of 30-90 nM, FsC[Fe 3+ ]-PL-2 has a good linear relationship with the aggregation degree of AuNPs, the linear equation is y=0.0115x-0.1538, and the correlation coefficient is 0.9941. 3+ ]-PL-2 concentration was considered to be the optimal concentration for inducing AuNPs aggregation.
[0133] In the actual detection of Campylobacter jejuni, in order to eliminate the negative charge of the Ca / Apt-MNPs surface aptamer on FsC[Fe 3+ ]-PL-2, and finally determined the FsC[Fe 3+ The optimal working concentration of ]-PL-2 was 106 nM.
[0134] FsC[Fe 3+]-PL-2 Detection Sensitivity
[0135] 600 μg / mL Ca / Apt-MNPs and 1.0 mL of bacteria were added at a density of 1.0×10 7 , 1.0×10 6 , 1.0×10 5 , 1.0×10 4 , 1.0×10 3 , 1.0×10 2 jejuni with 1.0×10,0 CFU / mL were vortexed and incubated in a constant temperature oscillator at 37°C for 30 min. After the incubation, magnetic separation was performed, the supernatant was removed, and the cells were washed 2-3 times with PBS buffer and ddH 2 O and washed twice. Add 200 μL of the optimal working concentration of FsC[Fe 3+ ]-PL-2, incubated in a constant temperature oscillator at 37°C for 30 minutes. After the incubation, magnetic separation was performed, and 100 μL of the supernatant and 100 μL of the AuNPs solution were vortexed and mixed respectively. The color was developed for 5 minutes, and finally the plates were placed in a 96-well plate to measure the UV-visible absorption spectrum at 400-750 nm.
[0136] like Fig.24 As shown in A, when the density of Campylobacter jejuni bacteria is higher than 10 4 CFU / mL, the absorption peak at 520nm in the UV-visible absorption spectrum of AuNPs gradually increased, the absorbance ratio (ΔA625 / A520) gradually decreased, the degree of AuNPs aggregation gradually weakened, tended to be more dispersed, and the color gradually changed from blue-purple to wine red. However, when the bacterial density was 10-10 4 CFU / mL range, the maximum absorption peak appeared at 625nM, the color of AuNPs solution was stable in blue-purple, and the absorbance ratio (ΔA625 / A520) was greater than 1( Fig.24 B). This result can prove that FsC[Fe 3+ ]-PL-2 assembled sensors cannot detect cell densities below 10 4 CFU / mL of Campylobacter jejuni showed a lower detection sensitivity.
[0137] FsC[Fe 3+ ]-PL-3 working concentration optimization
[0138] First, 100 μL of AuNPs with the best working concentration was mixed with 100 μL of FsC[Fe 3+]-PL-2 solution was vortexed to make the final concentration (0, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 mM). Then vortexed, color developed for 5 min at room temperature, and finally placed in a 96-well plate and measured using an ELISA reader at 400-750 nm. When the ratio of AuNPs to A625 / A520 reached the maximum, FsC[Fe 3+ ]-PL-3 concentration is the optimal concentration for aggregating AuNPs.
[0139] like Fig.25 As shown in A, with the FsC[Fe 3+ ]-PL-3 concentration increases, the absorption peak at 520nm in the UV-visible absorption spectrum of AuNPs gradually red-shifts to 625nm, the absorbance ratio (ΔA625 / A520) gradually increases, and the color gradually changes from wine red to blue purple. 3+ When the concentration of ]-PL-3 reached 45 nM, AuNPs were completely aggregated, the system became stable, and the absorbance ratio (ΔA625 / A520) no longer increased (e.g. Fig.25 B) In the concentration range of 20-45 nM, FsC[Fe 3+ ]-PL-3 and the aggregation degree of AuNPs have a good linear relationship, the linear equation is y = 0.1437x + 0.2983, and the correlation coefficient is 0.9928. 3+ ]-PL-3 concentration was considered to be the optimal concentration for inducing AuNPs aggregation.
[0140] In the actual detection of Campylobacter jejuni, in order to eliminate the negative charge of the Ca / Apt-MNPs surface aptamer on FsC[Fe 3+ ]-PL-3, and finally determined the FsC[Fe 3+ The optimal working concentration of ]-PL-3 was 52 nM.
[0141] FsC[Fe 3+ ]-PL-3 Detection Sensitivity
[0142] First, 600 μg / mL Ca / Apt-MNPs and 1.0 mL of bacteria with a density of 1.0×10 7 , 1.0×10 6 , 1.0×10 5 , 1.0×10 4 , 1.0×10 3 , 1.0×10 2jejuni with 1.0×10,0 CFU / mL were vortexed and incubated in a constant temperature oscillator at 37°C for 30 min. After the incubation, magnetic separation was performed, the supernatant was removed, and the cells were washed 2-3 times with PBS buffer and ddH 2 O and washed twice. Add 200 μL of the optimal working concentration of FsC[Fe 3+ ]-PL-3, incubated in a constant temperature oscillator at 37°C for 30 minutes. After the incubation, magnetic separation was performed, and 100 μL of the supernatant and 100 μL of the AuNPs solution were vortexed and mixed respectively. The color was developed for 5 minutes, and finally the plates were placed in a 96-well plate to measure the UV-visible absorption spectrum at 400-750 nm.
[0143] like Fig.26 As shown in A, when the density of Campylobacter jejuni bacteria is higher than 10 5 CFU / mL, the absorption peak at 520nm in the UV-visible absorption spectrum of AuNPs gradually increased, the absorbance ratio (ΔA625 / A520) gradually decreased, the degree of AuNPs aggregation gradually weakened, tended to be more dispersed, and the color gradually changed from blue-purple to wine red. However, when the bacterial density was 10-10 5 CFU / mL range, the maximum absorption peak appeared at 625nM, the color of AuNPs solution was stable in blue-purple, and the absorbance ratio (ΔA625 / A520) was greater than 1( Fig.26 B). This result can prove that FsC[Fe 3+ ]-PL-3 assembled sensors can only detect cells with a density higher than 10 5 CFU / mL of Campylobacter jejuni showed extremely low detection sensitivity.
[0144] Campylobacter jejuni binds to FsC[Fe 3+ ]-PL efficiency
[0145] The optimal working concentration of FsC[Fe 3+ ]-PL-1, FsC[Fe 3+ ]-PL-2, FsC[Fe 3+ ]-PL-3 were respectively 7 CFU / mL of Campylobacter jejuni was incubated in a constant temperature oscillator at 37°C for 30 min. After the incubation, a high-speed centrifuge was used to centrifuge at 12,000 rpm for 10 min to separate the supernatant. The remaining FsC[Fe 3+ ]-PL concentration, and the activity of Campylobacter jejuni against FsC[Fe 3+ ]-PL binding efficiency.
[0146] The results are as follows Fig. 27As shown, within 30 min, Campylobacter jejuni was 3+ ]-PL-1 binding efficiency was as high as 85%. With the increase of PL modification amount, Campylobacter jejuni had a stronger affinity for FsC[Fe 3+ ]-PL-2, FsC[Fe 3+ ]-PL-3 binding efficiency was significantly reduced, which further confirmed that Campylobacter jejuni 3+ ]-PL-1 has a higher binding efficiency.
[0147] Example 3 Working conditions and performance of colorimetric biosensor
[0148] Optimization of incubation time of Ca / Apt-MNPs and Campylobacter jejuni
[0149] First, 600 μg / mL of Ca / Apt-MNPs was mixed with 1 mL of bacteria with a density of 1.0×10 7 CFU / mL of Campylobacter jejuni were vortexed and incubated in a constant temperature oscillator at 37°C for 4, 8, 12, 16, 20 and 24 minutes, respectively. After the incubation, magnetic separation was performed to separate the supernatant, and finally the number of Campylobacter jejuni remaining in the supernatant was determined by qPCR absolute quantification method.
[0150] Fig.28 It is the number of bacteria remaining in the supernatant solution after Ca / Apt-MNPs capture Campylobacter jejuni during incubation for 0-20 minutes. When the incubation time is 12 minutes, the number of bacteria remaining in the supernatant solution is the lowest. As time goes by, the number of bacteria does not change significantly. Therefore, the optimal incubation time of Ca / Apt-MNPs is 12 minutes.
[0151] FsC[Fe 3+ Optimization of incubation time of PL-1 and Campylobacter jejuni
[0152] First, 600 μg / mL of Ca / Apt-MNPs was mixed with 1.0 mL of bacteria with a density of 1.0×10 7 jejuni at 100 CFU / mL were vortexed and incubated in a constant temperature oscillator at 37°C for 30 min. After the incubation, magnetic separation was performed, the supernatant was removed, and the cells were washed 2-3 times with PBS buffer and ddH 2 O and washed twice. 200 μL of 264 nM FsC[Fe 3+]-PL-1, incubated in a constant temperature oscillator at 37°C for 5, 10, 15, 20, 25, and 30 minutes respectively. After incubation, magnetic separation was carried out, and 100 μL of the supernatant was respectively aspirated and vortexed with 100 μL of AuNPs solution, and the mixture was color developed for 5 minutes. Finally, the plates were placed in a 96-well plate and the UV-visible absorption spectrum at 400-750 nm was measured to examine the effect of binding time on the absorbance ratio (ΔA625 / A520).
[0153] like Fig.29 As shown, for FsC[Fe 3+ After optimizing the binding time of FsC[Fe 3+ The optimal incubation time of ]-PL-1 and Campylobacter jejuni was 15 min.
[0154] FsC[Fe 3+ ]-Optimization of color development time of PL-1 and AuNPs
[0155] Take 100 μL of 240 nM FsC[Fe 3+ ]-PL-1 was vortex mixed with 100 μL of 2.8 nM AuNPs solution and colored for 1, 2, 3, 4, 5, and 6 min, respectively. Finally, the solution was placed in a 96-well plate and the UV-visible absorption spectrum at 400-750 nm was measured to examine the effect of binding time on the absorbance ratio (ΔA625 / A520).
[0156] like Fig.30 As shown, for FsC[Fe 3+ The time for AuNPs to develop color induced by ]-PL-1 was optimized. It can be seen that the absorbance ratio (ΔA625 / A520) of AuNPs gradually increased with the increase of color development time. At 4 minutes, the absorbance ratio reached the highest point, at which time AuNPs were completely aggregated. Therefore, the optimal color development time of AuNPs is 4 minutes.
[0157] Investigation of the detection methodology of Campylobacter jejuni based on nanogold biosensor
[0158] Detection limit of the sensor
[0159] First, 600 μg / mL of Ca / Apt-MNPs was mixed with 1.0 mL of bacteria with a density of 1.0×10 7jejuni at 100 CFU / mL were vortexed and incubated in a constant temperature oscillator at 37°C for 12 min. After the incubation, magnetic separation was performed, the supernatant was removed, and the cells were washed 2-3 times with PBS buffer and ddH 2 O and washed twice. 200 μL of 264 nM FsC[Fe 3+ ]-PL-1, incubated in a constant temperature oscillator at 37°C for 15 minutes. After the incubation, magnetic separation was performed, and 100 μL of the supernatant and 100 μL of the AuNPs solution were vortexed and mixed respectively. The mixture was color developed for 4 minutes, and finally placed in a 96-well plate to measure the UV-visible absorption spectrum at 400-750 nm.
[0160] The results are as follows Fig.31 As shown in A, when the density of Campylobacter jejuni is 10 2 -10 7 CFU / mL, the color of the AuNPs solution changed from blue-purple to wine red, and the UV-visible absorption spectrum showed obvious changes. 2 CFU / mL is the turning point, which can be regarded as the detection limit observable by naked eyes. However, at 0-10 CFU / mL, the color is close to blue. Combined with the relationship between the logarithm of Campylobacter jejuni bacterial density and the absorbance ratio of AuNPs (ΔA625 / A520) ( Fig.31 B) and found that the bacterial density was 10-10 7 When the CFU / mL was between ΔA625 / A520 and bacterial density, the linear regression equation was y=-0.122x+1.3102, and the linear correlation coefficient was R 2 The theoretical detection limit is 1 CFU / mL.
[0161] Specificity of the sensor
[0162] First, 600 μg / mL of Ca / Apt-MNPs was mixed with 1.0 mL of bacteria with a density of 1.0×10 7 CFU / mL of Campylobacter jejuni and other strains (Bifidobacterium, Escherichia coli, Salmonella enteritidis, Streptococcus gordonii, Listeria monocytogenes, Lactobacillus casei, Lactobacillus johnsonii, Enterococcus faecalis, Ralstonia putreii, and Shigella dysenteriae) were vortexed and incubated in a constant temperature oscillator at 37°C for 12 min. After the incubation, magnetic separation was performed, the supernatant was removed, and the cells were washed 2-3 times with PBS buffer and ddH2O. 2 O and washed twice. 200 μL of 264 nM FsC[Fe 3+]-PL-1, incubated in a constant temperature oscillator at 37°C for 15 minutes. After the incubation, magnetic separation was performed, and 100 μL of the supernatant and 100 μL of the AuNPs solution were vortexed and mixed respectively. The color was developed for 4 minutes, and finally the plates were placed in a 96-well plate to measure the UV-visible absorption spectrum at 400-750 nm.
[0163] The results are as follows Fig.32 As shown in the figure, when the detection system was used to detect Campylobacter jejuni, the AuNPs solution was wine red and in a dispersed state. The absorption peak at 520nm in the UV-visible absorption spectrum did not show a red shift, and the absorbance ratio (ΔA625 / A520) was less than 1. However, when the detection system was used to detect other control strains (Bifidobacterium, Escherichia coli, Salmonella enteritidis, Streptococcus gordonii, Listeria monocytogenes, Lactobacillus casei, Lactobacillus johnsonii, Enterococcus faecalis, Ralstonia putreii and Shigella dysenteriae), the absorption peak at 520nm in the UV-visible absorption spectrum of AuNPs was red-shifted to 625nm, and the absorbance ratio (ΔA625 / A520) was greater than 1, indicating that the AuNPs were completely aggregated. The experimental results show that the detection system based on Ca / Apt-MNPs, FsC[Fe 3+ This detection method of ]-PL-1 and AuNPs has high specificity in detecting Campylobacter jejuni.
[0164] Testing of actual samples
[0165] Take 100g of thawed chicken breast and soak it in 100mL of ddH 2 The chicken surface matrix was suspended in ddHO by stirring. 2 O water. Take 10mL of the suspension and add Campylobacter jejuni of a determined bacterial concentration, stir and let stand for 5 minutes. Take the supernatant and dilute it with PBS buffer for a certain multiple and vortex mix it with 600μg / mL Ca / Apt-MNPs solution, shake and incubate it in a 37℃ constant temperature metal bath for 30 minutes. After the incubation, magnetic separation is performed, the supernatant is removed, and it is washed with PBS buffer 2-3 times, and ddH 2 O and washed twice. 200 μL of 264 nM FsC[Fe 3+ ]-PL-1, incubated in a constant temperature oscillator at 37°C for 15 minutes. After the incubation, magnetic separation was performed, and 100 μL of the supernatant and 100 μL of the AuNPs solution were vortexed and mixed respectively. The color was developed for 4 minutes, and finally the plates were placed in a 96-well plate to measure the UV-visible absorption spectrum at 400-750 nm.
[0166] As the concentration of Campylobacter jejuni in chicken and milk increased, the color of AuNPs gradually turned red, and the absorbance ratio (ΔA625 / A520) gradually decreased. Finally, the recovery rate test was performed. The experimental results are shown in Table 1. The total detection time was 31 minutes, the recovery rate was 70-99%, and the actual detection limit was 7 CFU / mL. Therefore, the sensor can realize the rapid quantitative detection and analysis of Campylobacter jejuni in actual samples.
[0167] Table 1 Sensor detection of Campylobacter jejuni in simulated samples
[0168]
[0169]
[0170] Data are expressed as mean ± standard deviation, n = 3. abcde, data with different symbols are significantly different
[0171] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A colorimetric biosensor, characterized in that: include: A capture module comprises a magnetic nanoparticle and an aptamer modified on the magnetic nanoparticle, wherein the aptamer can specifically bind to Campylobacter jejuni; A binding-transduction module, for binding Campylobacter jejuni, comprising an iron carrier and polylysine modified on the surface of the iron carrier; Color development module, gold nanoparticle solution.
2. The colorimetric biosensor according to claim 1, wherein: The sequence of the aptamer is shown in SEQ ID NO.
1.
3. The colorimetric biosensor according to claim 1, wherein: The capture module also includes calcium ions, which are used to seal free carboxyl groups on the surface of the capture module; Alternatively, the capture module can be prepared by preparing the magnetic nanoparticles into a dispersion, adding a carboxyl activator to the dispersion, then adding an aptamer, and incubating the dispersion at 2-6°C.
4. The colorimetric biosensor according to claim 1, wherein: The iron carrier is derived from Aureobasidium melanogenum HN6.2 strain.
5. The colorimetric biosensor according to claim 1, wherein: The molar ratio of the iron carrier to polylysine is 1:1-3, preferably 1:1.0-1.
2.
6. The colorimetric biosensor according to claim 1, wherein: The preparation method of the binding-conducting module is as follows: a carboxyl activator is added to a polylysine solution for activation, an iron carrier is added for amide condensation reaction, and dialyzation is performed to obtain the binding-conducting module.
7. The colorimetric biosensor according to claim 1, wherein: The concentration of AuNPs solution is 1.0~3.0nM.
8. Use of the colorimetric biosensor according to any one of claims 1 to 7 in the colorimetric detection of Campylobacter jejuni.
9. The use according to claim 8, characterized in that: The solution of the capture module is first incubated with the sample containing Campylobacter jejuni to be tested, and then a first magnetic separation is performed. After removing the supernatant, the solution of the binding-conduction module is added for a second incubation, and then a second magnetic separation is performed. The supernatant after the second magnetic separation is added to the color development module for color development.
10. The use according to claim 9, characterized in that: The solution of the capture module has a concentration of 580-620 μg / mL; Alternatively, the first incubation time is 11 to 13 minutes; Or, during the second incubation, the concentration of the binding-transduction module in the incubation system is 240 to 270 nM; Alternatively, the second incubation time is 15 to 30 minutes, preferably 15 to 16 minutes. ; Or, the color development time is 4 to 5 minutes.